2017
DOI: 10.1007/s40272-017-0233-5
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia: Treating Pain in the Juvenile Patient

Abstract: Presently, evidence for the efficacy of medications for the treatment of juvenile fibromyalgia syndrome (JFMS) is limited. While there are medications approved by the US Food and Drug Administration (duloxetine, milnacipran and pregabalin) for adults with fibromyalgia syndrome, there are none for the treatment of JFMS. A variety of medications have been prescribed for the treatment of JFMS, including (but not limited to) non-opioid analgesics, opioids, anticonvulsants, antidepressants, and muscle relaxants. Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 111 publications
0
15
0
2
Order By: Relevance
“…JFMS begins in youngsters and is increasingly diagnosed in adolescents. [1][2][3] At present, 2-6.1% of school-age children are thought to have JFMS. 4,5 Juvenile fibromyalgia syndrome often persists for years without diagnosis, with most patients referred to specialists for chronic headaches and chest or abdominal pain symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…JFMS begins in youngsters and is increasingly diagnosed in adolescents. [1][2][3] At present, 2-6.1% of school-age children are thought to have JFMS. 4,5 Juvenile fibromyalgia syndrome often persists for years without diagnosis, with most patients referred to specialists for chronic headaches and chest or abdominal pain symptoms.…”
mentioning
confidence: 99%
“…6 Although fibromyalgia syndrome (FMS) is the known lead to important morbidity in adults, its effects in childhood were not well known until recently with studies on the topic beginning to emerge. [1][2][3]7 As FMS can be associated with chronic somatic and psychological symptoms in adults, it is important that it is correctly identified and treated during adolescence. 6,8,9 As acknowledged in the literature, increased pain, fatigue, and depression symptoms and reduced quality of life (QoL) are seen in children with JFMS compared to healthy children and children with rheumatic disorders.…”
mentioning
confidence: 99%
“…As a result, wide practice variations may exist in how pediatric rheumatologists treat patients with JPFS. A variety of classes of medications (e.g., opioids, non-opioid analgesics, anticonvulsants, antidepressants, muscle relaxants) have been tried for treating symptoms of JPFS despite limited efficacy studies [7]. Nonpharmacological treatments, particularly physical therapies (PT) and training in cognitive-behavioral pain coping skills, have more established empirical support for improving symptoms and functioning in JPFS [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…CWP and FMS demonstrated female predominance [95], with juvenile FMS affecting females four times more than males [29]. This female predominance is incompletely understood, but likely involves genetic, psychological, behavioral (including reporting behavior), and neurobiological factors [68].…”
Section: Resultsmentioning
confidence: 99%
“…There are no validated criteria or evidence-based consensus guidelines for the diagnosis of juvenile FMS [2830]. Ting et al [31] concluded that the 2010/2011 American College of Rheumatology fibromyalgia criteria [25] had diagnostic applicability in adolescent females; however, there are no published studies of juvenile FMS which have applied the 2016 revisions to the 2010/2011 fibromyalgia criteria [29].…”
Section: Introductionmentioning
confidence: 99%